The PqsR and RhlR Transcriptional Regulators Determine the Level of Pseudomonas Quinolone Signal Synthesis in Pseudomonas aeruginosa by Producing Two Different pqsABCDE mRNA Isoforms - Brouwer, Stephan (J Bacteriol, 2014)
Regulation of gene expression plays a key role in bacterial adaptability to changes in the environment. An integral part of this gene regulatory network is achieved via quorum sensing (QS) systems that coordinate bacterial responses under high cellular densities. In the nosocomial pathogen Pseudomonas aeruginosa, the 2-alkyl-4-quinolone (pqs) signaling pathway is crucial for bacterial survival under stressful conditions. Biosynthesis of the Pseudomonas quinolone signal (PQS) is dependent on the pqsABCDE operon, which is positively regulated by the LysR family regulator PqsR and repressed by the transcriptional regulator protein RhlR. However, the molecular mechanisms underlying this inhibition have remained elusive. Here, we demonstrate that not only PqsR but also RhlR activates transcription of pqsA. The latter uses an alternative transcriptional start site and induces expression of a longer transcript that forms a secondary structure in the 5′ untranslated leader region. As a consequence, access of the ribosome to the Shine-Dalgarno sequence is restricted and translation efficiency reduced. We propose a model of a novel posttranscriptional regulation mechanism that fine-tunes PQS biosynthesis, thus highlighting the complexity of quorum sensing in P. aeruginosa.